PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KEBERMAKNAAN BELAJAR PADA PEMBELAJARAN JARAK JAUH PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Evi Nurhayati; Aris Fauzan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this research was to find out the implementation of a project-based learning model in improving meaningful learning in distance learning on PAI sub lesson "Mari Ikhlas Beramal" in SDN Pereng and SDN 2 Cucukan, Prambanan in 2021. The variable of the target of change was meaningful learning seen from the improvement of mastery of concepts, learning activities, responses, and critical thinking skills of the students with a project-based learning model. This research was classroom action research using a cycle model consisting of two cycles. The research subjects were 18 students of grade V SDN Pereng, and 25 students of grade V. Data collection techniques used observation of learning activities and documentation. Data analysis techniques used qualitative analysis models. The research results from cycle to cycle obtained an increase in the meaningful learning at grade V in Sub-Lesson "Mari Ikhlas Beramal” after the implementation of classroom actions using a project-based learning model.